2017
DOI: 10.5539/elt.v10n6p1
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Myths of the Native and Non-Native English Speakers Teachers (NESTs & NNESTs) on Saudi EFL Tertiary Students

Abstract: Many people believe the myth that being taught by a native speaker is the best way to learn a language. This belief has influenced many Saudi schools, language institutes, and universities to include the nativeness factor as part of a language instructor's job requirements. Using an open ended questionnaire, this study aims to investigate the impact of native English speaking teachers (NESTs) and non-native English speaking teachers (NNESTs) on EFL university Saudi students. It also explores how the teachers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 14 publications
(55 reference statements)
5
39
2
Order By: Relevance
“…This belief, while benefiting native-English-speaking teachers, also creates pressures on their part as well as on other teachers including Saudi teachers and students. This emotion(al) labor tends to be overlooked in the existing literature, which places non-native-English-speaking teachers at the center of inquiry and projects them as those who are on the receiving end of native-speakerism (Alghofaili and Elyas, 2017; Park, 2017; Song and Park, 2019). As we show below, the teacher participants in our study—Westerners, native speakers of English, experienced, and qualified—also undergo their own emotion(al) labor, which is often unacknowledged by those around them and by scholarly work.…”
Section: Emotion(al) Labor In Response To Social Religious and Cultmentioning
confidence: 99%
“…This belief, while benefiting native-English-speaking teachers, also creates pressures on their part as well as on other teachers including Saudi teachers and students. This emotion(al) labor tends to be overlooked in the existing literature, which places non-native-English-speaking teachers at the center of inquiry and projects them as those who are on the receiving end of native-speakerism (Alghofaili and Elyas, 2017; Park, 2017; Song and Park, 2019). As we show below, the teacher participants in our study—Westerners, native speakers of English, experienced, and qualified—also undergo their own emotion(al) labor, which is often unacknowledged by those around them and by scholarly work.…”
Section: Emotion(al) Labor In Response To Social Religious and Cultmentioning
confidence: 99%
“…Such outcomes agree with lots of other outcomes that showed that NESTs were recommended to instruct speaking because of their precise eloquence and accent such as (Al-Omrani, 2008;Arva & Medgyes, 2000;Lee, 2004;Moussu, 2010;Samimy & Brutt-Griffler, 1999;Tang, 1997). Although it is not consistent with many of findings, which affirmed that instructors nativeness and former works have no notable influences on the EFL Saudi learners' acquisition processes (e.g., Alghofaili & Elyas, 2017). Nevertheless, Wardak (2014) obviously shows that NES and NNES instructors are equally competent, and potent to instruct at more advanced levels.…”
Section: Discussionmentioning
confidence: 88%
“…To realize the instructing method of the instructors can make a discrepancy in how instructors set their courses, how they treat the students, and how well their subjects do in the realizing content (Conti, 1989, p. 88). While the results of Alghofaili & Elyas (2017) showed that instructors' native quality and presuppositions have no notable efficacy on the EFL Saudi learners' acquisition methods. And instead they attributed success in teaching to some other characteristics such as teachers' competence and experience, instructors sharing the learners' L1 play proper roles in the EFL acquisition process, instructors accent and teacher's personality.…”
Section: Native and Non-native English Speaking Instructing Styles Anmentioning
confidence: 89%
“…As the debate continues in the field of TESOL, this paper considers the matter from the EFL learners' perspective in the Saudi context. The last two decades have seen exponential growth in the number of research studies that aimed to determine the characteristics of an ideal language teacher (Al-Nawrasy, 2013;Alghofaili & Elyas, 2017).…”
Section: Introductionmentioning
confidence: 99%